Analysis of the Implementation of PSAK 109 Concerning Accounting for Zakat, Infaq, and Alms at the Amil Zakat, Infaq, and Alms Institution (LAZISNU) PCNU Sidoarjo for the 2020-2022 Period - Firda Amelia; Luqita Romaisyah (Institut Agama Islam Negeri Lhokseumawe, 2024)
The increasing realization of zakat in Indonesia must be balanced with good management of zakat, infaq, and sadaqah funds by the standards set by the accounting standards board, namely Statement of Accounting Standards 109 (PSAK 109), which regulates the management of zakat, infaq, and alms accounting. This research will analyze whether LAZISNU PCNU Sidoarjo has implemented PSAK 109 in managing its zakat, infaq, and alms funds. The research method used in this research is qualitative descriptive research. This research uses primary and secondary data, with data collection procedures through observation, interviews, documentation, and literature study. The data analysis technique is done by compiling the data obtained and then organizing and selecting important data to conclude. The research results show that LAZISNU PCNU Sidoarjo still needs to implement PSAK 109 as a whole. In managing ZIS funds, LAZISNU PCNU Sidoarjo has implemented PSAK 109 but not completely, because LAZISNU PCNU Sidoarjo has not fully met the standards for disclosing ZIS funds, and only presents financial reports in the form of fund change reports. However, in presenting the fund change report, LAZISNU Sidoarjo separated ZIS and non-halal funds.